Nutritional Value of Fish: Lipids, Proteins, Vitamins, and Minerals. Issue 2 (3rd April 2018) - Khalili Tilami, Sarvenaz; Sampels, Sabine
ABSTRACT: The present review aims to give a concise review about important nutrients from fish and their impact on human health. In addition, possible effects of rearing system and feeding on the most vulnerable group of nutrients, the lipids, are summarized. Fish are considered as nutritionally valuable part of the human diet and consumption two times a week is recommended, mostly due to the content of long chain polyunsaturated n-3 fatty acids. These fatty acids are essential in human nutrition and have proven to be involved in many metabolic functions. Among others, they have anti-inflammatory effects, decrease platelet aggregation and are essential parts in the cell membranes, cardiovascular system, brain, and nervous tissue. In addition the proteins, peptides and amino acids from fish became more recently known for having positive health effects. Furthermore fish is also a rich source of certain vitamins and minerals as Vitamin D, selenium, phosphorus, and calcium. It should be highlighted that, when considering nutrition and related health aspects, it is impossible to focus one group of nutrients separately. Most probably the discussed effects of fish on human health are due to the consumption of the fish as a whole and hence the combination of all present nutrients.